The Pivotal Role of a Lawyer in Combating Official Corruption in Nigeria - Ushie James Ebuara (Rechtsidee, 2016)
Nigeria is ranked internationally as one of the most corrupt nations in the world. As embarrassing as this status is, it is indeed the reality of our situation. The general public and now even the executive arm of the Federal government have continued to question how members of the legal profession discharge their role in applying the law because they have absolute belief in the law as their protection against the tendencies that are depriving them of their well being, dehumanizing them and even threatening the existence of their country, they waited for the law to respond to these tendencies by putting them in check, stop them completely or control them, they have watched helplessly the inability of law to effectively respond to these tendencies and have watched the tendencies continue unabated and escalated into the conditions we found ourselves today The purpose of this paper is to examine the role of lawyers as Judges, as Prosecutors and defence Attorneys in promoting and encouraging corruption in our body politics. It further examines in contrast the role lawyers should play in the renewed fight against corruption. Lawyers as agents of social change should be in the vanguard for the reorientation of the mind set of Nigerian in the renewed fight against corruption and social rebirth generally. To effectively play this role members of the legal profession must purge themselves of corrupt tendencies and must be seen to be above board.